2011
DOI: 10.1159/000323310
|View full text |Cite
|
Sign up to set email alerts
|

Switching from Neural Networks (PAPNET) to the Imager (Hologic) for Computer-Assisted Screening

Abstract: Objective: The large set of ThinPrep slides prepared in the Leiden Cytology and Pathology Laboratory is exploited for calculating the impact of the transition from PAPNET neural network scanning to the Imager technology. Study Design: All cervical samples were suspended and fixed in the coagulant fixative BoonFix. We compared 57,541 ThinPrep slides which were scanned by PAPNET and 64,273 ThinPrep slides processed with the Imager: 99,157 cases originated from the Dutch population screening program of asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In fact, whole‐slide digital cytology will profit enormously from artificial intelligence–based diagnostic algorithms. In the past, several attempts were made with automated screening systems, 44 , 45 , 46 which were based on glass slides. Applying artificial intelligence to virtual slides may open new perspectives, reducing the strain of the screening activity and helping in the interpretation of slides in the context of large population‐based screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, whole‐slide digital cytology will profit enormously from artificial intelligence–based diagnostic algorithms. In the past, several attempts were made with automated screening systems, 44 , 45 , 46 which were based on glass slides. Applying artificial intelligence to virtual slides may open new perspectives, reducing the strain of the screening activity and helping in the interpretation of slides in the context of large population‐based screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PAPNET was used for comparative studies involving human papillomavirus-related molecular tests 31 with colposcopy techniques 71 and has been compared with other non-ANN-based semiautomated screening systems, such as the Imager® by Hologic® 72 or the AutoPap® Guided System. 52 Cervix is not the sole organ of the female reproductive system.…”
Section: Anns In Gynecological Cytopathology the Papnet Systemmentioning
confidence: 99%
“…Thereafter, the ThinPrep Imaging System (TIS) (Hologic, Bedford, MD, USA) and the FocalPoint GS Imaging System (Becton Dickinson, Burlington, NC, USA) were introduced for primary screening in 2004 and 2008, respectively, to complement proprietary (i.e., ThinPrep and SurePath) thin-layers and to facilitate final case reporting using Bethesda nomenclature. 2 Comparative studies by Boon et al 11 in 2010 reported significantly higher odds ratios for detecting abnormal cells in the ASCUS, CIN I-II, and CIN III+ diagnostic categories, and notably in asymptomatic routinely screened women, thus they concluded improved abnormal cell detection rates may be realized when applying TIS on ThinPrep thin-layers relative to PAPNET.…”
Section: Introductionmentioning
confidence: 99%